INSURGENCIES: COMPETITION FOR RESOURCES AS AN EXPLANATORY VARIABLE (Journal of the Spanish Institute for Strategic Studies, 2013)
Over the course of recent years, we have witnessed a proliferation of scientificarticles that defend a stance explaining the nature of and the violencecommitted by insurgent movements, focusing on factors of an economicsense. The intention in this discourse is to set forth a different focus; not oneinspired by greed and preying on public and assets arising from the conflict,but rather on the result of a rational choice that is agreed on by an insurgentgroup when it sees its survival threatened and it loses its monopoly situationover the population from which it aims to win support for its cause .